The Influence of Consumer Behavior on Purchasing Decisions of Martabak Manis - Zubaidah Warni; Tri Fatrie Fatmawati; Pantani Dahlan (Almana : Jurnal Manajemen dan Bisnis, 2022)
Abstract: Martabak Manis is a culinary delight that is liked by many sellers, especially in Kayu Agung, Ogan Komering Ilir Regency, with varying prices. This research was conducted on Martabak Manis sellers in Kayu Agung Ogan Komering Ilir by surveying and interviewing 30 Martabak Manis sellers and 530 Martabak Manis buyers who became the population of this study while the sample was drawn using the Slovin formula so that there were 85 people. This study uses a causal relationship, namely a causal relationship where one variable (independent) influences another variable (dependent). The data analysis technique uses simple linear regression analysis. The results of the simple regression test show that consumer behavior influences purchasing decisions. Based on the coefficient of determination test, consumer behavior has a positive and significant effect on purchasing decisions.